Characteristics of Crime in Kočevje Municipality - Hacin, Rok (10. Nacionalna konferenca o varnosti v lokalnih skupnostih: Mirna, varna in inkluzivna družba ter varnost v lokalnih skupnostih, 2024)
In the paper, we focus on the characteristics of crime in the Kočevje municipality. Based on data on crime and population, we determined crime trends in Kočevje municipality and Slovenia in the period 2000–2023. We analyzed the number of crimes, crime rates, and crime indexes. On average, crime in Kočevje municipality represents approximately one percent of all crime in Slovenia. A comparison of crime trends highlighted differences between Kočevje municipality and Slovenia. Crime rates in Kočevje municipality were mostly higher than the national average. The analysis of individual types of crimes (crime rates) showed that in Kočevje municipality, the scope of violent and sexual crime is greater, compared to the national level. In contrast, the extent of economic crime and crimes against legal traffic at the national level is significantly higher. The findings confirmed the impact of factors deriving from the local environment on the scope and characteristics of crime.